Correlations between infant mortality and recommended immunization schedules against vaccine–preventable diseases in Slovenia: Primerjava med vzroki za umrljivost dojenčkov in cepljenjem med rednim programom cepljenja v Sloveniji - Zemljič, Mateja; Pejković, Božena; Kranjc, Ivan; Kraigher, Alenka (Acta Medico-Biotechnica, 2021)
Purpose: The infant mortality rate (IMR) is among the most important indicators of a nation's health and well–being. In Slovenia, over the last 55 years, infant mortality (IM) has decreased rapidly and vaccinations are undoubtedly the major contributing factor. In Slovenia, infant immunization is initiated at the age of 3 months. The vaccination schedule includes several doses of combined vaccines that should be administered according to the yearly program on immunization.Methods: In this retrospective study, 279 infants were divided into subgroups in accordance with the vaccination program. The structure of the study design used the data of the National Institute of Public Health of Slovenia regarding the causes of IM for the years 2007–2011Results: Direct and indirect leading causes of death were infant respiratory distress syndrome (n = 22), extreme immaturity (n = 19), necrotizing enterocolitis (n = 18), extremely low birth weight (n = 14), and hypoplastic left heart syndrome (n = 14). The maximum IMR (85.30%) occurred before the recommended vaccination period. During the prescribed program of vaccination, the IMR was 14.70%.Conclusion: Genetic alterations, congenital abnormalities, and preterm birth complications are the major and leading causes of IM. Most instances of IM occur within the first two months of life, before the recommended vaccinations. During the recommended vaccination period, IM is low and causes of death are largely congenital and genetic diseases. The results of the comparative study during the recommended vaccination schedule by the end of the first year of life from 2007 to 2011 substantiates that the vaccines are not a major cause of IM.